PENGARUH MOTIVASI INSTRINSIK DAN EKSTRINSIK TERHADAP KINERJA KARYAWAN PT. BEST DENGAN BUDAYA ORGANISASI SEBAGAI VARIBEL MODERASI - irawan, andriyan; Paulus wardoyo; Wyati Saddewisasi (Universitas Semarang, 2025)
Performance is related to improving the quality of work, to improve the quality of work must touch three aspects, namely: ability, enthusiasm, and dedication. Those with high performance, will always be passionate or eager to work. Performance achievement itself is influenced by many factors including intrinsic motivation, extrinsic and organizational culture. Intrinsic and extrinsic motivation is a driver of morale which will ultimately lead to employee performance. Work motivation which is very influential on the performance of an employee can certainly be realized because of the company's organizational culture that is able to generate (moderate) the motivation of the employee both intrinsically and extrinsically. This research is an explanatory research. The number of samples in the study was 87 people. The sampling technique used stratified proportional random sampling. This study uses a questionnaire that has been tested for validity and reliability. The results of this study indicate that organizational culture is able to moderate the influence of intrinsic motivation and extrinsic motivation on employee performance